Antifatigue properties of tanshinone IIA in mice subjected to the forced swimming test. (1st January 2017) - Lin, Chueh-Yu; Jhang, Yan-Shu; Lai, Shang-Chi; Chen, En-Li; Lin, I-Hsin; Chang, Tung-Wu; Tseng, Yu-Wei; Seenan, Vaishnavi; Shiung, Jane; Chen, Ming-Hua; Chiang, Yun-Chen; Chen, Tsung-I; et al.
Abstract: Context: Tanshinone IIA (Tan IIA) is a constituent of Danshen Salvia miltiorrhiza Bunge (Lamiaceae); however, its antifatigue activity remains unclear. Objective: To study the antifatigue properties of Tan IIA and its underlying mechanisms. Materials and methods: In program I, three mouse groups were separately subjected to three gavages with 0, 1 and 6 mg/kg Tan IIA and forced swimming test (FST) weekly for 8 weeks; in program II, one gavage with 0, 2 and 10 mg/kg Tan IIA was administered plus FST weekly for 4 weeks. Serum glucose, lactate, superoxide dismutase (SOD), malondialdehyde (MDA) and blood urea nitrogen (BUN) were determined after final FST. Results: Tan IIA significantly prolonged swimming durations in program I but not in program II. Swimming times were 3208 ± 1054 and 2443 ± 1054 s for the 1 and 6 mg/kg treatments and 856 ± 292 s for the vehicle control. The two doses significantly reduced serum glucose levels (40.3 ± 8.5 and 60.0 1 ± 11.8 mg/kg) and lactate levels (61.3 ± 27.5 and 68.8 ± 8.5 mg/kg) in treated mice compared with those in control mice (137.5 ± 38.6 mg/kg and 122.7 ± 18.2 mg/kg, respectively). However, no significant differences were observed regarding SOD, MDA or BUN levels. Discussion and conclusions: Tan IIA has antifatigue activity and is associated with reductions in serum glucose and lactate levels. Further studies should assess muscle hypertrophy and efficient aerobic glycolysis caused by Tan IIA. Tan IIA has potential as a pharmacological agent for fatigue resistance.